Guidelines for a research information system at the University of Moa, Cuba - Suárez-Fernández, Digna; Nicot, Beatriz Reyes; González, María Josefa Peralta; Piedra-Salomón, Yelina; Leiva-Mederos, Amed (Advanced Notes in Information Science, 2024)
Despite the efforts made at the University of Moa “Dr. Antonio Núñez Jiménez”, Cuba, to improve information management, difficulties persist in its collection, integration, and recovery for the processing and dissemination of the results of the institutional scientific activity and the evaluation of research. This article presents guidelines to be considered for the implementation of a research information system. Research methods and techniques were applied, such as analysis of bibliographic information, structured interviews, questionnaires, participant observation, and benchmarking. For business modeling and requirements education, the logical stages of computerized information systems development were used as references. The implementation of research information systems in the Cuban university context allows an integral and efficient management of the processes related to research management, which contributes to improve the quality and efficiency of the scientific activity in the academic institutions of the country.